Analysis of The Relationship Between Workload and Stress In Emergency Department Nurses - Wuri Triyanti, Anjayani; Marcella, Marcella; Pranata, Satriya; Mubin, Fatkhul (Jurnal Indonesia Sosial Sains, 2025)
Emergency Department (ED) nurses are frontline healthcare providers who must remain ready 24 hours a day to deliver rapid emergency services. High workload and complex cases often lead to work-related stress that affects both the quality of nursing care and nurse well-being. This study aims to analyze the relationship between workload and stress levels among ED nurses through a systematic literature review. The review included 10 research journals published within the last five years that used quantitative or mixed-method designs and focused on ED nurses in hospital settings. Data were analyzed descriptively with critical appraisal to assess article quality and relevance. Findings show that ED nurse workload varies, with light workload ranging from 15.9%–68.8%, moderate workload 17.5%–69.7%, and heavy workload 0%–60%. A significant relationship was identified between workload and work stress. High workload, including large patient volumes, high task intensity, and case complexity, increases physical and psychological pressure on nurses, triggering stress. Workload is influenced by internal factors (gender, age, education, length of service) and external factors (patient numbers, nurse–patient ratio, work systems, facilities). Productive and non-productive nursing activities also contribute. The study concludes that workload significantly affects ED nurse stress. Hospitals must balance workload with nurses’ abilities, while nurses require adequate skills to manage emergency care demands.